Biocultural Diversity in Indigenous Conservation (International Journal of Animal Biodiversity, Conservation and Systematics ( IJABC), 2025)
Biocultural diversity -- the integrated suite of linguistic, cultural, and biological diversity that co-evolves in human communities embedded in their environments -- is increasingly recognised as a conservation asset: indigenous and local communities often maintain traditional ecological knowledge (TEK) systems and land management practices that sustain biodiversity at levels comparable to or exceeding formally protected areas. Yet the relationship between biocultural diversity, biodiversity outcomes, and conservation governance remains poorly quantified at systematic scales. This study analysed 247 indigenous and local community conservation territories (ICCAs) across 24 countries, comparing biodiversity metrics (vertebrate species richness, threatened species density, and ecosystem integrity index) between ICCAs with high biocultural diversity (intact language, active TEK transmission, and strong governance institutions; n = 84), ICCAs with moderate biocultural diversity (n = 84), and matched adjacent state-protected areas (n = 79). High-biocultural-diversity ICCAs showed species richness 34.7% higher than state-protected areas of equivalent area (p < 0.001) and 18.4% higher than low-biocultural-diversity ICCAs (p < 0.001). Threatened species density was 47.4% higher in high-biocultural ICCAs than in state PAs, confirming that community territories provide disproportionate habitat for species of conservation concern. TEK application score -- a standardised measure of active traditional land and wildlife management -- was the strongest single predictor of biodiversity outcome (beta = +0.47, p < 0.001), exceeding protected area legal status, enforcement capacity, and funding level as predictors. These results provide quantitative evidence for the biodiversity value of biocultural diversity and argue for its systematic integration into GBF 30x30 protected area expansion planning.